Optimasi Lingkungan Permukiman Padat Perkotaan Melalui Program KKN-T Di RT 01 Jalan Sudirman III Kelurahan Pintu Batu - Talafebher, Dos-q Cincin; Liandra, Viko; Charles, Reno; Wulandari, Nora; Saputra, Virdian; Trianggana, Dimas Aulia; Haryono, Mimpira; Karmanita, Deti (Jurnal Dehasen Untuk Negeri, 2026)
The community of RT 01 Jalan Sudirman III, Pintu Batu Sub-district, is a densely populated urban settlement in the center of Bengkulu City that faces environmental problems such as unmanaged household waste, air pollution, limited green open space, and high traffic accident risk at blind-spot corners and intersections. The Thematic Community Service Program (KKN-T) of Universitas Dehasen Bengkulu was implemented to optimize the quality of this settlement environment through a series of interventions, including the installation of neighborhood navigation maps and emergency numbers, convex mirrors and reflective road markings, routine community clean-up activities, educational signage, environmental awareness campaigns, and the distribution of plant seedlings suitable for narrow spaces. The method consisted of situation analysis, problem identification with local partners, participatory program planning, field implementation over one month, and evaluation with follow-up plans involving local actors. The results indicate improved awareness of cleanliness and safety, a reduction of waste accumulation at several points, better traffic safety at blind-spot areas, and the emergence of small-scale greening initiatives that enhance the aesthetics and comfort of the neighborhood. These findings show that KKN-T in RT 01 Jalan Sudirman III contributed to optimizing a dense urban settlement environment through the synergy of simple technical interventions, continuous environmental education, and active community participation